Splenomegaly in Children and Adolescents - Suttorp, Meinolf; Classen, Carl Friedrich (Frontiers in Pediatrics, 2021)
Abstract In contrast to other lymphoid tissues making up the immune system, the spleen as its biggest organ is directly linked into the blood circulation. Beside its main task to filter out microorganism, proteins, and overaged or pathologically altered blood cells, also humoral and cellular immune responses are initiated in this organ. The spleen is not palpable during a physical examination in most but not all healthy patients. A correct diagnosis of splenomegaly in children and adolescents must take into account age-dependent size reference values. Ultrasound examination is nowadays used to measure the spleen size and to judge on reasons for morphological alterations in associated with an increase in organ size. An enormous amount of possible causes has to be put in consideration if splenomegaly is diagnosed. Among these are infectious agents, hematologic disorders, infiltrative diseases, hyperplasia of the white pulp, congestion, and changes in the composition and structure of the white pulp by immunologically mediated diseases. This review attempts to discuss a comprehensive list of differential diagnoses to be considered clinically in children and young adolescents.